PENERAPAN PENEGAKAN HUKUM DISIPLIN POLRI DEMI TERWUJUDNYA GOOD GOVERNANCE AND CLEAN GOVERMENT DALAM RUANG LINGKUP POLDA JAWA TENGAH - Nenny Probowati; Gunarto Gunarto (Jurnal Hukum Khaira Ummah, 2018)
The problem studied in this research is about the implementation of law enforcement of POLRI discipline based on Good Goverment and Clean Goverment to the members in POLDA Central Java and the weakness and solution to the implementation of law enforcement of POLRI discipline to the POLDA members of Central Java in order to realize Good Goverment and Clean Goverment.The method used in this research is with socio-legal research approach that comes from collecting data obtained from primary data and secondary data, then analyzed by qualitative analysis method.The results of this study ultimately provide an answer that the implementation of POLRI discipline based on Good Governance and Clean Goverment against members in POLDA Central Java is as the process of law enforcement in general in the process of law enforcement of police members against Central Java Police members are inseparable from the five factors comprise from legal factors, law enforcement factors, facilities and infrastructure, society and culture other than that weaknesses and solutions to the implementation of law enforcement discipline POLRI to the members of POLDA Central Java for the realization of Good Governance and Clean Goverment, related to the weakness is the legal awareness of members of the Police is still less and the environment / association is also a weak factor of enforcement of discipline, the solution is the conceptual law enforcement and law enforcement as a process must be realized by 1) Increasing the quality of Provost Police Investigators 2) Increasing awareness and kepa Polri's staff against discipline and 3) Procurement and management of supporting facilities for enforcement of Discipline Law.Suggestions from this research are to the police institution is expected to create more programs related to coaching members to minimize violations of police discipline and create members in accordance with the ideals of the police in order to realize the image of good and clean police.Keywords: Law Enforcement, Police Discipline, Good Governance and Clean Goverment.